Attitude-Orbit Integrated Control for Spacecraft Fly-Around Mission Based on Chebyshev Neural Network - Sun, Qian; Jia, Yingmin (IEEE transactions on aerospace and electronic systems, 2024)
This article investigates the attitude-orbit integrated control for the spacecraft fly-around mission with a non-cooperative target. The dual quaternion approach is employed to formulate the concise attitude-orbit coupled motion model of the uncertain servicing spacecraft. To address parametric uncertainties and unknown disturbances, we propose an estimation algorithm based on the Chebyshev neural network. Using the estimated variables, two nonsingular fast terminal sliding mode (NFTSM) controllers without and with actuator saturation are developed. Besides, we achieve anti-unwinding control by introducing an auxiliary variable into the NFTSM surface. It is proven in the Lyapunov sense that the attitude and position tracking errors converge to the bounded sets in finite time. Numerical simulations are carried out to validate the proposed control scheme.